CALIFORNIA ENCEPHALITIS VIRUS ISOLATIONS FROM YUKON MOSQUITOES, 1971 - McLEAN, DONALD M.; GODDARD, EDWARD J.; GRAHAM, ELIZABETH A.; HARDY, GLENNA J.; PURVIN-GOOD, KEITH W. (Oxford University Press, 1972)
McLean, D. M. (Dept. Microbiology, Univ. of British Columbia, Vancouver 8, B.C., Canada), E. J. Goddard, E. A. Graham, G. J. Hardy and K. W. Purvin-Good. California encephalitis virus isolations from Yukon mosquitoes, 1971. Am J Epidemiol 95: 347–355, 1972.—California encephalitis virus strains were isolated from 12 of 84 pools of Aedes canadensis mosquitoes collected principally near Whitehorse (61N, 135W), Yukon Territory, Canada between June 18 and July 19, 1971, with a peak isolation rate of 30% (8 of 27 pools) collected from July 16–19. The initial Yukon isolate, Marsh Lake 23, appeared antigenically identical with the 1969 Grey Sage strain from southern British Columbia. Marsh Lake 23 and other Yukon isolates were antigenically identical to the Montana snowshoe hare subtype of California encephalitis virus by im-munodiffusion tests. Marsh Lake 23 virus multiplied after intrathoracic injection of Yukon Aedes canadensis mosquitoes and domestic A. aegypti. California encephalitis neutralizing antibodies were detected in 160 of 1313 (12%) of Yukon mammals collected between May 22 and August 12, including 76 of 298 (25%) Lupus americanus and 80 of 970 (8%) Citellus undulatus . Hemagglutination inhibition antibodies to group B arbo-viruses were found in 91 of 1313 (7%) mammals, but only sera from 7 C. undulatus among 91 inhibitory sera neutralized either Powassan, St. Louis encephalitis or both viruses.